TO THE QUESTION OF GOALS AND OBJECTIVES ROMAN PUBLIC LAW IN THE WRITINGS OF ANTONIO GUARINO - Baizakov, Адиль Талгатович; Saginaev, Мейржан Егинбаевич (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
The article will consider the main goals and objectives of Roman public law, reflected in the works of the outstanding Italian lawyer - novelist Antonio Guarino. In his works on Roman jurisprudence, Professor Guarino studied not only Roman private law, but also the concept and content of Roman public law. And also, Professor Guarino in his writings pays special attention to the issue of limiting the powers of Roman magistrates who exercised executive and judicial power. Since the problems of Roman public law are poorly covered in modern legal science, the works of Professor Guarino become relevant for us in the field of constitutional law (in the field of human rights protection). The purpose of this article is to analyze the limitation of the powers of Roman magistrates in Roman public law. The objectives of the article are a brief analysis of Roman criminal law, the study of the nature of magistrate edicts, the disclosure of the role of the people's tribunate in limiting state power. The article will apply the formal legal method, as well as general scientific methods of cognition, which include analysis, synthesis, deduction, induction, comparative method, historical method. In the course of the research, this article will analyze and consider the issues of limiting the powers of public authorities in Roman public law. The results obtained can be used in the field of constitutional law and in the protection of human and civil rights. It should be noted that the works of the Italian novelist Antonio Guarino in the field of Roman public law are of great interest to legal science. His theoretical developments and ideas may be useful for improving the legal system of Kazakhstan.